The Peter F. Drucker reader : selected articles from the father of modern management thinking. - Drucker, Peter F. (Peter Ferdinand), 1909-2005 (Boston, Massachusetts : Harvard Business Review Press, 2017)
Peter Drucker revolutionized management thinking before there was management thinking. For nearly half a century he inspired and educated managers--and powerfully shaped the nature of business--with his landmark articles in Harvard Business Review. Through Drucker's unique lens, this volume presents a rare opportunity to trace the evolution of the great shifts in organizations and to grasp more firmly the role of managers in the ongoing effort to balance change with continuity. The book also offers managers and executives a collection of best practices as well as introspective questions that will help them improve as organizational leaders. Infused with a perspective that holds new relevance today, these selections reveal a celebrated thinker at his best. Drucker paints a clear and comprehensive picture of management thinking and practice--both as it is and as it will be.--
What makes an effective executive -- The theory of the business -- Managing for business effectiveness -- The effective decision -- How to make people decisions -- They're not employees, they're people -- The new productivity challenge -- What business can learn from nonprofits -- The new society of organizations -- Managing oneself.
Description based on print version record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Industrial management -- History; Management -- History; Industrial management; Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books